Magnetic resonance imaging assessment of body composition parameters in Crohn's disease. Issue 8 (August 2020) - Labarthe, Ghislain; Dolores, Michael; Verdalle-Cazes, Mikael; Charpentier, Cloé; Roullee, Pauline; Dacher, Jean-Nicolas; Savoye, Guillaume; Savoye-Collet, Céline
Abstract: Background: Body composition, currently evaluated by computed tomography scan, is related to poor evolution and severity of Crohn's disease (CD). Few MRI studies have been performed, yet it is the most commonly used imaging modality for the surveillance of the disease. Aim: Evaluate the feasibility of MRI body composition measurement and compare the variation according to the activity of the disease. Methods: A cohort of 132 consecutive patients was studied. The visceral adiposity index (VAI), subcutaneous adiposity index (SAI) and skeletal muscle index (SMI) were measured. Patients were divided into 2 groups according to disease activity. Sarcopenic status was defined according to the cut off value (SMI < 38.9 cm 2 /m 2 in women and < 54.4 cm 2 /m 2 in men). Results: MRI measurements of body composition parameters were feasible and reproducible. After adjustment, sarcopenia was more common (2.07 [1.02; 4.27], p = 0.046), and the SMI (−4.90 [−9.36; −0.431], p = 0.032) was lower in active disease. The SAI was lower (−14.7 [−29.8; 0.258], p = 0.054) in active disease. The VAI tended to be higher with active disease (3.91 [−3.50; 11.9], p = 0.34), and the VAI/SAI+VAI ratio was higher (9.40 [4.72; 14.1], p <0.001). Conclusion: Assessment of body composition is feasible and reproducible in routine MR and parameters are related to disease activity.